Decoupling of maternal and neonatal inflammatory levels at the maternal-fetal interface: evidence from a population-based proteomic study - Milazzo, Floriana; Gigase, Frederieke; Suleri, Anna; Amreen, Bushra; D’Souza, Darwin; Kim-Schulze, Seunghee; Bergink, Veerle; de Witte, Lot; Lesseur, Corina; Rommel, Anna-Sophie (Frontiers in Immunology, 2026)
BackgroundMaternal inflammation during pregnancy has been linked to offspring physical and neurodevelopmental health. This association has been hypothesized to operate through fetal immune responses. Yet, population-based evidence exploring the relationship between maternal and neonatal inflammation remains limited. This study investigates the associations of maternal inflammatory markers measured in the third trimester and at birth with neonatal inflammatory profiles at birth.MethodsInterleukin (IL)-1β, IL-6, IL-17a (pg/mL), and CRP (mg/L) levels were measured in maternal plasma at birth and in the third trimester and standardized for the at-birth and third-trimester subset. In the neonates, 92 inflammatory markers were measured in Dried Blood Spots using Olink®. We used linear regression models with empirical Bayes moderation to investigate the association between maternal inflammatory marker levels at each timepoint and neonatal inflammatory marker levels. We adjusted for maternal factors, child factors, and technical factors. We applied the false discovery rate (FDR-adjusted p-value <0.05) to adjust results for multiple comparisons.ResultsMaternal IL-1β, IL-6, IL-17a, and CRP levels measured at birth (n=194 mother-child dyads) or in the third trimester (n=235) were not significantly associated with levels of any of the 92 neonatal inflammatory markers. Effect estimates were small, and no associations survived FDR correction (FDR <0.05). Findings were observed with robust parsimonious adjustment for covariates and were similar across both maternal sampling timepoints.ConclusionMaternal inflammation measured at birth and in the third trimester was not significantly associated with widespread changes in neonatal peripheral inflammatory profiles. These findings suggest that low-grade maternal inflammation may not elicit detectable systemic inflammatory responses in neonates at birth in a general population sample. Future research should replicate our findings and assess the role of neonatal inflammatory markers in subsequent offspring health outcomes.